Evaluasi Sistem Pengendalian Internal Pengeluaran Kas Pada Kantor Kecamatan Kempas Kabupaten Indragiri Hilir - Ayu Safitri; Novriani Susanti; Ranti Melasari (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2026)
This study examines the compliance of cash disbursement systems and procedures, as well as the implementation of internal control, in relation to the effectiveness of the performance at the Kempas Sub-District Office, Indragiri Hilir Regency. The high volume of financial transactions and administrative demands require an orderly cash disbursement system and adequate internal management to ensure accuracy and regulatory compliance. This research evaluates the implementation of cash disbursement systems and internal control using a qualitative approach through interviews, observations, and documentation. The analysis indicates that the cash disbursement system has been operating effectively in accordance with Minister of Home Affairs Regulation No. 77 of 2020, and internal control has been implemented following Government Regulation No. 60 of 2008. However, aspects such as human resource development, routine evaluation of controls, and the publication of financial performance information still require improvement. This study recommends enhancing human resource management, conducting periodic control evaluations, and improving financial information transparency to maintain the effectiveness and accountability of public services.